1988
DOI: 10.1143/jjap.27.1885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Content of the Magnetic and Electric Properties of Electroless Ni–P Film after Heat Treatment

Abstract: The magnetic and electric properties of electroless Ni–P films after heat treatment are investigated as a function of the P content in the deposit. The residual Ni, which means the surplus Ni (crystallized Ni) after Ni3P formation, is confirmed to determine the film properties of resistivity and saturation magnetization. Moreover, they depend only on the P content and are independent of the preparation conditions. The saturation magnetization, M s, and the reciprocal of resistivity, ρ-1, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
4

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 26 publications
2
13
0
4
Order By: Relevance
“…The phosphorus content in the coating layers can be controlled by the deposition parameters, such as pH value, bath composition, etc. [9][10][11][12]. The phase of coating layer with low phosphorus is microcrystalline, which is consistent with the results of Marshall et al [13] and Mai [14].…”
Section: Resultssupporting
confidence: 85%
“…The phosphorus content in the coating layers can be controlled by the deposition parameters, such as pH value, bath composition, etc. [9][10][11][12]. The phase of coating layer with low phosphorus is microcrystalline, which is consistent with the results of Marshall et al [13] and Mai [14].…”
Section: Resultssupporting
confidence: 85%
“…The phosphorus content in the coating layer can be controlled by the deposition parameters, such as pH value, bath composition, etc. [15][16][17][18] The phase of coating layer with low phosphorus is microcrystalline, which is consistent with the results of Marshall et al [19] and Mai [20] They found that the nickel-phosphorus phase depended on the phosphorus content, and if the phosphorus content was between 3 and 7 wt pct, the phase was microcrystalline, amorphous between 7 and 9 wt pct. Figure 7 shows the XRD patterns of as-obtained NCFs annealed at different temperatures in vacuum.…”
supporting
confidence: 80%
“…[85] It has been found that the P content and the thermal history determine the structure and properties of the electroless Ni layer. [108][109][110][111][112][113][114][115] In general, as-plated electroless Ni(Ni-P) layer is amorphous at high P contents (P greater than about 10 at.%) and tends to undergo self (or thermal)-crystallization on annealing. There are no significant compositional changes during crystallization.…”
Section: Detailed Interface Microstructure Of Solder Bumpmentioning
confidence: 99%